PERAN KUA DALAM MENGATASI NIKAH SIRI DI KECAMATAN BALIKPAPAN TIMUR KOTA BALIKPAPAN - Azhar, Muh Zaim; Alisyah, Muh Fuad Rifqie (STIT Ibnu Rusyd Tanah Grogot, 2024)
This study examines the role of the Office of Religious Affairs (Kantor Urusan Agama or KUA) in East Balikpapan in addressing unregistered marriages (nikah siri). The occurrence of nikah siri is primarily attributed to the lack of public awareness regarding the negative impacts that may arise after such marriages, as well as administrative issues that do not comply with the regulations established by the KUA. Therefore, the KUA consistently strives to conduct public outreach and coordinate with subdistrict and village heads, as well as neighborhood heads (RT) in the local area. Additionally, Islamic religious counselors play a significant role in supporting the KUA by providing education and information to the public regarding KUA programs, particularly the socialization of the potential consequences of nikah siri.